(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract Many people in the Philippines like eating food, particularly when it is sweet, flavorful, and nutritious. It is the ideal combo for individuals who want to indulge while staying healthy. This is what makes Filipinos so passionate about it. On the other hand, Saba bananas grow in massive bunches at the apex of huge banana palms’ tall central stems. In comparison to the common banana, they are short and thick. Regarding cuisine and flavour, Saba bananas have a complex flavour profile that, when cooked, takes on a sweet potato-like flavour. When they’re ripe, the sweetness comes into play. This study aims to determine the quality of our product and its shortcomings using input from respondents and relevant research. The respondents of this study, the demographic and sample, the instrument utilized, how the researchers validated the instrument, the technique for data collection, and the statistical treatment of data in this study all used quantitative research design. The researchers will use a formula to arrive at a possible solution by tallying or computing the results. This study aims to determine how acceptable sweet banana balls with toppings are. The following findings were drawn: most respondents are between 17 and 19. The respondents considered taste, texture, presentation, and price acceptable. The taste of sweetness, the texture of the product, the presentation of the product, and the pricing were all reasons for respondents to purchase the product. The researchers are conducting this research to see if this product may be marketed. The study’s findings will assist us, as researchers, in improving the quality of our product, such as taste, size, sweetness, and so on.